Business and Professional Income Under the Personal Income Tax (Book). - Zeff, Stephen A.; Sommerfeld, Ray M. (The Accounting Review, 1965)
Reviews the book "Business and Professional Income Under the Personal Income Tax," by C. Harry Kahn.